Análise espaço-temporal de uso e cobertura da terra na bacia hidrográfica do rio São Francisco - Lima, Alexandre Herculano de Souza (2019)
In Brazil there is a large availability of water resources, however the distribution of these resources does not occur in an equitable manner. Along with the issue of water scarcity, deforestation is revealed as another harmful environmental issue in river basins. In this context of problems, the São Francisco River basin is inserted, the largest hydrographic basin fully included in Brazilian territory. The geotechnologies based on the approach to landscape ecology enable assertive analyzes to manage areas with the problems of the São Francisco River basin. Thus, the objective of this work is to carry out a spatio-temporal analysis of land use and cover and size classes of forest fragments in the São Francisco River Basin, based on data from MAPBIOMAS, from the 1997s, 2007 and 2017. The mapping of land use and land cover was prepared using QGIS 2.18 software, as well as the calculation of the area and quantity of forest fragments that were divided into the following size classes: 1 - small (up to 10 ha); 2 - medium (between 10 and 100 ha) and 3 - large (greater than 100 ha). The results show that the hydrographic basin has undergone intense changes in its dynamics of land use and coverage and the structure of its forest fragments over 20 years, with emphasis on: areas of the Atlantic Forest with increased forest regeneration and large fragments; the agricultural frontier of Western Bahia and mesoregions of the São Franciscan Valley of Bahia and São Francisco Pernambucano with increased deforestation rates and small fragments; and an increase in forest maintenance spread in the Middle São Francisco, often associated with forestry.